Com vistas á liberdade: fugas escravas e estratégias de inserçao social do fugido nos últimos decênios do século XIX, em Minas Gerais - Geosiane Mendes Machado (2010)
We aim on this dissertation to understand the insertion strategies of the runaway slaves in Minas Gerais in the last decades of the nineteenth century. The time lapse is from 1871, the year of the Free Birth Law promulgation and, as the last mark, the year of 1888 with slavery extinction in Brazil. This side view was substantial to realize the changes in the runaway slaves profile as well as the opportunities offered by the labor market of labored specialties, railways and civil constructions, military activities universe and the effort of improvement of the urban centers, altogether as spaces for the fugitives insertion. We focused our research on understanding the behavior of the slaves in escape and the various tactics of insertion used by them on their attempt for freedom in Minas Gerais. We realized in this research that there was a specific profile of the runaway slaves in Minas Gerais at the end of the nineteenth century. The escape was considered a way of resistance, constantly practiced by slaves who had seen the possibility of negotiation within the slave quarters fading away. Therefore, we used periodic from Ouro Preto, the province governors reports, besides the polices documentation and some criminal trials which involved some fugitive slaves, revealing several and complex strategies of their resistance. They cheated the authorities and remained among the mass of free, gained and rental slaves as if they were free.